2022
DOI: 10.1002/alz.12530
|View full text |Cite
|
Sign up to set email alerts
|

Late‐life physical activity relates to brain tissue synaptic integrity markers in older adults

Abstract: Introduction Physical activity (PA) is widely recommended for age‐related brain health, yet its neurobiology is not well understood. Animal models indicate PA is synaptogenic. We examined the relationship between PA and synaptic integrity markers in older adults. Methods Four hundred four decedents from the Rush Memory and Aging Project completed annual actigraphy monitoring (Mean visits = 3.5±2.4) and post mortem evaluation. Brain tissue was analyzed for presynaptic proteins (synaptophysin, synaptotagmin‐1, v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 51 publications
1
23
1
Order By: Relevance
“…Synaptic protein. Synaptic integrity was quantified as average levels of six synaptic proteins previously shown to demonstrate significant relationships with physical activity (SNAP-25, complexin-I, synaptophysin, synpatotagmin-1, syntaxin, VAMP) (Casaletto et al, 2021).…”
Section: Postmortem Indicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Synaptic protein. Synaptic integrity was quantified as average levels of six synaptic proteins previously shown to demonstrate significant relationships with physical activity (SNAP-25, complexin-I, synaptophysin, synpatotagmin-1, syntaxin, VAMP) (Casaletto et al, 2021).…”
Section: Postmortem Indicesmentioning
confidence: 99%
“…We monitored objective activity levels via accelerometerbased actigraphy in older adults during life who completed autopsy with brain tissue quantified for immunohistochemistrybased microglial activation markers (anti-human HLA-DP-DQ-DR, plus morphology staging) as part of the Rush Memory and Aging Project (MAP). Prior MAP studies demonstrate that actigraphybased physical activity is associated with better cognitive trajectories, reduced incidence of Alzheimer's dementia (Buchman et al, 2012(Buchman et al, , 2018, and higher levels of synaptic proteins in brain tissue (Casaletto et al, 2021). We aimed to characterize the relationship between late life physical activity and markers of microglial activation in MAP participants, including regional and pathology-specific effects.…”
Section: Introductionmentioning
confidence: 99%
“…Synapse-related genes are extensively downregulated in multiple brain regions in both aging and AD [ 72 ]. Furthermore, greater physical activity is associated with higher levels of synaptic integrity markers, including synaptophysin, synaptotagmin-1, vesicle-associated membrane proteins, syntaxin, and complexin-I, in the brain of older adults [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis across 12 cohorts including thousands of participants also concluded that physical activity significantly protected against cognitive decline, even at low to moderate levels (Sofi et al, 2011). A recent study found that late-life physical activity was associated with higher presynaptic protein levels, known to positively affect cognition (Casaletto et al, 2021). Indeed, recent meta-analyses of randomized controlled trials using physical activity interventions reveal notable protective effects for dementia risk (Beckett, Ardern, & Rotondi, 2015; Xu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%